2020
DOI: 10.1002/emp2.12301
|View full text |Cite
|
Sign up to set email alerts
|

System impacts of the COVID‐19 pandemic on New York City's emergency medical services

Abstract: Objectives: To describe the impact of the COVID-19 pandemic on New York City's (NYC) 9-1-1 emergency medical services (EMS) system and assess the efficacy of pandemic planning to meet increased demands. Methods: Longitudinal analysis of NYC 9-1-1 EMS system call volumes, call-types, and response times during the COVID-19 peak-period (March 16-April 15, 2020) and postsurge period (April 16-May 31, 2020) compared with the same 2019 periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 23 publications
3
45
2
Order By: Relevance
“…In New York City, planned interventions to prioritize high‐acuity calls resulted in increases in the time from the call assignment to the arrival of the EMS vehicle at the scene by 3 min for severe cases and by 11 min for minor cases. 3 The transport time from the scene to the hospital and the time from the arrival to the hospital to the next dispatch were also extended. In Italy, the time between arriving to the hospital and entering the emergency department was extended in Bergamo and Brescia to 32 and 15 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In New York City, planned interventions to prioritize high‐acuity calls resulted in increases in the time from the call assignment to the arrival of the EMS vehicle at the scene by 3 min for severe cases and by 11 min for minor cases. 3 The transport time from the scene to the hospital and the time from the arrival to the hospital to the next dispatch were also extended. In Italy, the time between arriving to the hospital and entering the emergency department was extended in Bergamo and Brescia to 32 and 15 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory distress related EMS calls increased during the early pandemic period ( 31 ). Our study adds to the existing literature by examining respiratory distress related EMS calls by race and ethnicity during the early pandemic period, January to June 2020, compared to the same time period in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…This was considered a panic phase because earlier outbreaks in the area had very little or close to zero infected patients, making the response to such situations different. In many countries, there is a significant increase in the use of EMS services, including phone calls, consultation, and an increasing number of operations [4], [7], [8], [9], [10], [11], [12]. However, in the areas studied, the amount of service usage dropped significantly with an average of 1-2 EMS operations per day as people were not willing to risk infection and stayed at home.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that the panic of infection among EMS personnel has increased, which is associated with increased risk of transmission to their family members [9]. In Israel, 8.51% of emergency calls were COVID-19 related, resulting in more than 4 times the typical use of emergency hotlines [10] similar to New York City [11] and Saudi Arabia [12]. A study in Japan found that the effects of this required hospitals allow for reduced delivery or increased coordination time in EMS [13].…”
Section: Introductionmentioning
confidence: 99%